Influência do pulso de inundação na fenologia foliar e conteúdo de clorofila em duas espécies da floresta de Igapó da Amazônia Central, Brasil - Maia, Lúcia Alencar (Acta Amazonica, 2020)
In order to verify the influence of flood-pulse dynamics on leaf phenology and concentrations of chlorophyll a, b and total, 15 individuals of two species typical of the black-water igapó forest, Eschweilera tenuifolia and Hevea spruceana, were studied in the lower course of the river Tarumã-Mirim, Amazonas, Brazil. Leaf phenology was followed weekly from July 1993 to Dezember 1994 and the chlorophyll content was measured in the laboratory every month. Variations in the chlorophyll contents were related to leaf age. Mean concentrations of total chlorophyll in mature and old leaves of E. tenuifolia were 473.5 and 288.6 mg m-2, and 418.5 and 199.0 mg m-2 in H. spruceana. The peak shedding and flush occurred during the aquatic phase.